The Role of Extra-Articular Tenodesis in Combined ACL and Anterolateral Capsular Injury. (4th October 2017) - Guenther, Daniel; Irarrázaval, Sebastián; Bell, Kevin M.; Rahnemai-Azar, Amir Ata; Fu, Freddie H.; Debski, Richard E.; Musahl, Volker
Abstract : Background: The "gold standard" treatment of anterolateral capsular injuries in anterior cruciate ligament (ACL)-deficient knees has not been determined. The purpose of this study was to determine the effects of ACL reconstruction and extra-articular reconstruction on joint motion in the ACL-deficient knee and in the combined ACL and anterolateral capsule-deficient knee. Methods: An anterior tibial load of 134 N and internal tibial torque of 7 Nm were applied to 7 fresh-frozen cadaveric knees using a robotic testing system continuously throughout the range of flexion. The resulting joint motion was recorded for 6 knee states: intact, ACL-deficient, ACL-reconstructed, combined ACL and anterolateral capsule-deficient, ACL-reconstructed + anterolateral capsule-deficient, and ACL-reconstructed + extra-articular tenodesis. Results: Anterior tibial translation of the ACL-reconstructed + anterolateral capsule-deficient knee in response to an anterior tibial load was restored to that of the intact knee at all knee-flexion angles (p > 0.05). However, for this knee state, internal tibial rotation in response to internal tibial torque was not restored to that of the intact knee at 60° or 90° of knee flexion (p < 0.05). For the knee state of ACL-reconstructed + extra-articular tenodesis, internal rotation in response to internal tibial torque was restored to the motion of the intact knee at each of the tested knee-flexion angles (p > 0.05). Compared with the intact knee, 2 of 7 specimens showed decreased internal tibial rotation with ACL reconstruction + extra-articular tenodesis. Conclusions: In this study, an extra-articular tenodesis was necessary to restore rotatory knee stability in response to internal tibial torque in a combined ACL and anterolateral capsule-deficient knee. The amount of rotatory knee instability should be carefully assessed to avoid over-constraint of the knee in these combined ligament-reconstruction procedures. Clinical Relevance: On the basis of our findings, the surgical procedure needs to be personalized depending on the amount of rotatory knee instability in the injured knee and the amount of rotation in the contralateral knee.